Suppressing glutamine metabolism in the pancreatic cancer microenvironment can enhance the anti-tumor effect of CD8 T cells and promote the efficacy of immunotherapy - Fan, Jun; Chen, Jianfei; Wang, Rui; Peng, Yisheng; Tan, Sunde; Zhang, Xi; Tang, Hao; Chen, Maoshan; Li, Bo; Yang, Xiaoli (Frontiers in Immunology, 2025)
ObjectiveThis study aims to investigate the relationship between tumor cell glutamine metabolism and CD8 T cells, with the goal of providing new insights to improve immunotherapy for pancreatic cancer.MethodsUsing the The Cancer Genome Atlas – Pancreatic Adenocarcinoma (TCGA-PAAD) cohort, we computed gene expression scores related to glutamine metabolism and stratified patients into high- and low-score groups. Prognosis and differences in immune cell anti-tumor activity were compared between these groups. We further utilized single-cell RNA sequencing data to quantitatively assess the expression of glutamine metabolism-related pathways in tumor cells. Based on tumor-specific glutamine metabolism gene expression, patients were again classified into high- and low-score groups. The immune remodeling effects exerted by tumor cell glutamine metabolism on CD8 T cells were subsequently investigated. To examine the impact of perturbing glutamine metabolism within the tumor microenvironment on CD8 T cell phenotype and the efficacy of PD-1 inhibitors, we conducted in vivo animal experiments.Resultswe analyzed the pancreatic cancer dataset in the cancer gene atlas database. We found that tumor glutamine metabolism was negatively correlated with patient prognosis and anti-tumor activity. Next, we defined two types of CD8 effector T cells in single-cell RNA sequencing data, namely, effector memory T cells (CD8-Tem) and terminally differentiated effector memory T cells (CD8-Temra). Under the pressure of high glutamine metabolism in tumor cells, the cytotoxicity of the CD8-Tem subset was reduced, and its immaturity score increased, while the exhaustion score of the CD8-Temra subset increased. Pseudotime analysis showed that CD8-Tn in the low-scoring group mainly developed into CD8-Tem subset, and its immune activation pathway was significantly upregulated. In addition, we found that the glutamine metabolism inhibitor JHU083 promoted the infiltration of CD4 and CD8 T cells and T lymphocyte differentiation, and increased the efficacy of PD-1 inhibitors. Glutamine inhibitors can inhibit the apoptosis of immune cells in the tumor microenvironment, while promoting CD8 T cells activation and cytotoxicity increase.ConclusionInhibition of glutamine metabolism within the pancreatic cancer microenvironment results in reduced apoptosis of immune cells, heightened activation and cytotoxicity of CD8 T cells, and a substantial enhancement in the therapeutic efficacy of immunotherapy.